Prognostic values of serum neuronal biomarkers NSE and protein S-100 in acute period of severe hypoxic-ischemic encephalopathy in term infants - Surkov, Denys (ScienceRise: Medical Science, 2018)
It remains unclear if the serum concentrations of neuron-specific enolase (NSE) and protein S-100 correlate with severity and possible complications of hypoxic ischemic encephalopathy (HIE) as well as monitoring parameters of cerebral perfusion and central hemodynamics in term newborns. The aim of research. To determine diagnostic and predictable values of NSE and protein S-100 in acute period of severe hypoxic-ischemic encephalopathy in neonates. Materials and methods. Data of 89 term infants with Apgar score at birth of seven or less and Sarnat stage II-III was collected during ≤72 hours of life. The correlation between NSE, S-100 and Glasgow Coma Scale, seizures, confirmed by the aEEG, the unwanted development of neurological complications such as cerebral leukomalacia, and the short-term clinical results were analyzed. Result. In acute period of HIE the concentration of serum neuronal biomarkers S-100 and NSE proteins substantially exceeds the reference values for the first hours after labor and exceeds the normal range until the 5th day of life. The dynamics of these data significantly changes during this period. Mostly diagnostically and prognostically significant the measurement of biomarkers was on the 3rd day of treatment, immediately after the end of the therapeutic hypothermia, at the beginning of rewarming and brain reperfusion, when both indicators were most closely correlated with the assessment of the GCS: NSE (r=-0.3; p=0.002 ) and S-100 (r=-0.3; p=0.003). The value of S-100 on day 1 correlating with the following unwanted development of leukomalacia is above 1.8 μg/L (p=0.002), which is more than 3 times higher from the reference level of 0.51 μg/L given by Simon-Pimmel J. (2017) for term newborns. Conclusion. The evaluation of the serum concentrations of protein S-100 and neuron-specific enolase in the acute period of hypoxic ischemic encephalopathy in the term newborns has a significant diagnostic and predictable value and correlates with the severity and short-term clinical results of HIE